PENILAIAN TINGKAT KESEHATAN LPD BERDASARKAN CAMEL (STUDI PADA LPD DESA PAKRAMAN KLONCING) - Dwi Ariawan, I Kadek Budi; Trisnadewi, Ni Kadek Ayu; Parma, I Putu Gede (Komunitas Manajemen Kompetitif, 2024)
The Village Credit Institution (LPD) is one of the financial institutions in Bali. The Covid-19 pandemic caused a decline in profits in 2020. Based on this, it is very important to pay attention to the health level of LPDs, where LPDs are institutions that concern the security of public funds. The aim of this research is to determine and analyze the health level of Village Credit Institutions in Pakraman Penasan Village, Banjarangkan District, Klungkung Regency during the 2019-2021 period which is reviewed using the CAMEL method (Capital, Assets, Management, Earnings and Liquidity). This type of research is qualitative research sourced from primary data and secondary data using interview, observation and documentation techniques. This research uses a data validity test using triangulation. The data analysis technique used is LPD financial report analysis using the CAMEL method in accordance with Bali Governor Regulation No. 44 of 2017. The research results show that the Pakraman Penasan Village LPD is in a healthy condition in 2020 and 2021 with a combined score in 2020 of 89.50, in 2021 of 90.00%. Meanwhile, 202 was in healthy condition with a combined score of 89.00%. From the results of this research, it can be recommended that the LPD of Pakraman Adat Kloncing Village pay attention to its distribution of funds.